Malaysian Female Pre-Service Teachers Online: Exploring Their Internet Use And Attitudes - Wong, Su Luan; Ng, Siew Fung; Tang, Sai Hong (2005)
This paper discusses the Internet use and attitudes of female pre-service teachers with differing levels of Internet experience. This study was conducted at Universiti Putra Malaysia (UPM), one of the premier universities in Malaysia and is an analysis of early returns of a large scale study. The study is exploratory in essence and seeks to ascertain the comfort level of female pre-service teachers where the Internet is concerned. This research found that female pre-service teachers used the Internet for many reasons and had positive attitudes toward this technology. The research also suggested that Internet experience can increase Internet use and encourage positive Internet attitudes. Experienced female Internet users tended to remain online longer than those with lesser experience. The more experienced they were, the more likely they would use it for information, entertainment and social reasons. In addition female pre-service teachers with longer Internet exposure had better control over the Internet. It is likely that they will integrate the new technology effectively in their classroom instruction as they are convinced of the benefits of the Internet either as a teaching tool or as a learning medium. According to past research, the tendency of those who have more positive attitudes, to use and integrate the Internet in their teaching-learning process in the classrooms is very high: The findings of this research proved encouraging as studies have clearly shown that the success of Internet utilization was very much related to the users' experience and attitudes toward the Internet.